An Activity of Thioacyl Derivatives of 4-Aminoquinolinium Salts towards Biofilm Producing and Planktonic Forms of Coagulase-Negative Staphylococci. (3rd May 2015) - Wojtyczka, Robert D.; Zięba, Andrzej; Dziedzic, Arkadiusz; Kępa, Małgorzata; Idzik, Danuta
Abstract : Microorganisms present in different environments have developed specific mechanisms of settling on various abiotic and biotic surfaces by forming a biofilm. It seems to be well justified to search for new compounds enabling biofilm reduction, which is highly resistant to antibiotics. This study was thus an initial assessment of the antibacterial activity of two new quinoline derivatives of a structure of 3-thioacyl 1-methyl 4-arylaminoquinolinium salts against coagulase-negative staphylococci (CoNS) isolated from a hospital environment, in a form of both biofilms and in planktonic form. Thirty-three stains of CoNS isolated from the hospital environment (air, surfaces) and seven reference strains from the ATCC collection were selected for the study. The mean MIC value for 1-methyl-3-benzoylthio-4-(4-chlorophenylamino)quinolinum chloride (4-chlorophenylamino derivative) was 42.60 ± 19.91  μ g/mL, and in the case of strains subjected to 1-methyl-3-benzoylthio-4-(4-fluorophenylamino)quinolinum chloride (4-fluorophenylamino derivative) activity, the mean MIC value was 43.20 ± 14.30  μ g/mL. The mean concentration of 4-chlorophenylamino derivative that inhibited biofilm formation was 86.18 ± 30.64  μ g/mL. The mean concentration of 4-fluorophenylamino derivatives that inhibited biofilm formation was higher and amounted to 237.09 ± 160.57  μ g/mL. Based on the results, both derivatives of the examined compounds exhibit high antimicrobial activity towards strains growing both in planktonic and biofilm form.